Efficacy and safety of left atrial appendage closure versus medical treatment in atrial fibrillation: a network meta-analysis from randomised trials. Issue 2 (1st September 2016) - Sahay, Shweta; Nombela-Franco, Luis; Rodes-Cabau, Josep; Jimenez-Quevedo, Pilar; Salinas, Pablo; Biagioni, Corina; Nuñez-Gil, Ivan; Gonzalo, Nieves; de Agustín, Jose Alberto; del Trigo, Maria; Perez de Isla, Leopoldo; Fernández-Ortiz, Antonio; et al.
Abstract : Background: The effectiveness of vitamin K antagonist (VKA) versus placebo and antiplatelet therapy (APT) is well established for stroke prevention in atrial fibrillation (AF). Non-vitamin K antagonist oral anticoagulants (NOAC) are mostly superior to VKA in stroke and intracranial bleeding prevention. Recent randomised controlled trials (RCTs) suggested the non-inferiority of percutaneous left atrial appendage closure (LAAC) versus VKA. However, comparisons between LAAC versus placebo, APT or NOAC are lacking. The purpose of this network meta-analysis was to assess the efficacy and safety of LAAC compared with other strategies for stroke prevention in patients with AF. Methods: We pooled together all RCTs comparing warfarin with placebo, APT or NOAC in patients with AF using meta-analysis guidelines. Two major trials of LAAC were also included and a network meta-analysis was performed to compare the impact of LAAC on mortality, stroke/systemic embolism (SE) and major bleeding in relation to medical treatment. Results: The network meta-analysis included 19 RCTs with a total of 87 831 patients with AF receiving anticoagulants, APT, placebo or LAAC. Indirect comparison with network meta-analysis using warfarin as the common comparator revealed efficacy benefit favouring LAAC as compared with placebo (mortality: HR 0.38, 95% CI 0.22 to 0.67, p<0.001; stroke/SE: HR 0.24, 95% CI 0.11 to 0.52, p<0.001) and APT (mortality: HR 0.58, 95% CI 0.37 to 0.91, p=0.0018; stroke/SE: HR 0.44, 95% CI 0.23 to 0.86, p=0.017) and similar to NOAC (mortality: HR 0.76, 95% CI 0.50 to 1.16, p=0.211; stroke/SE: HR 1.01, 95% CI 0.53 to 1.92, p=0.969). LAAC showed comparable rates of major bleeding when compared with placebo (HR 2.33, 95% CI 0.67 to 8.09, p=0.183), APT (HR 0.75, 95% CI 0.30 to 1.88, p=0.542) and NOAC (HR 0.80, 95% CI 0.33 to 1.94, p=0.615). Conclusions: The findings of this meta-analysis suggest that LAAC is superior to placebo and APT, and comparable to NOAC for preventing mortality and stroke or SE, with similar bleeding risk in patients with non-valvular AF. However, these results should be interpreted with caution and more studies are needed to further substantiate this advantage, in view of the wide CIs with some variables in the current meta-analysis.